2010
DOI: 10.1094/pdis-94-8-1055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watering Regime on Disease Development in Pinus sylvestris Seedlings Inoculated with Bursaphelenchus vallesianus and B. mucronatus

Abstract: Several Bursaphelenchus spp. have been detected in declining pine trees in Europe during intensive monitoring for the pine wood nematode B. xylophilus. We investigated the pathogenicity of B. vallesianus and B. mucronatus, isolated from declining Scots pine (Pinus sylvestris) forests in Valais (Switzerland), in relation to drought stress. Four isolates of B. vallesianus and two isolates of B. mucronatus were inoculated into 3-year-old P. sylvestris trees, which were subjected to different watering treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…More recently, a pathogenic potential of B. vallesianus was also observed in greenhouse conditions, where 2-year-old seedlings of three different pine species, Pinus nigra, P. brutia and P. pinea, were experimentally inoculated (Dayi & Akbulut, 2012). These findings supported the theory that overall mechanisms causing PWD are shared by all pathogenic Bursaphelenchus species, including B. vallesianus (Polomski & Rigling, 2010). Therefore, further investigations on B. vallesianus are needed to get broader insights into its biology, possible pathogenicity and evolutionary history, and thus to better understand its role in PWD development.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…More recently, a pathogenic potential of B. vallesianus was also observed in greenhouse conditions, where 2-year-old seedlings of three different pine species, Pinus nigra, P. brutia and P. pinea, were experimentally inoculated (Dayi & Akbulut, 2012). These findings supported the theory that overall mechanisms causing PWD are shared by all pathogenic Bursaphelenchus species, including B. vallesianus (Polomski & Rigling, 2010). Therefore, further investigations on B. vallesianus are needed to get broader insights into its biology, possible pathogenicity and evolutionary history, and thus to better understand its role in PWD development.…”
Section: Introductionsupporting
confidence: 64%
“…In contrast, involvement of a few other Bursaphelenchus species, for example B. mucronatus and B. sexdentati, in PWD development remains unclear. However, recent controlled experimental inoculations in greenhouse conditions showed that these species also possess a pathogenic potential (Polomski & Rigling, 2010;Dayi & Akbulut, 2012). Therefore, because of the detection of B. xylophilus in Europe, strategic programmes have been applied to monitor the distribution of Bursaphelenchus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mucronatus, B. sexdentati, B. leoni Baujard, B . h e l l e n i c u s S k a r m o u t s o s , B r a a s c h a n d Michalopoulou, B. vallesianus were also tested by using different tree species (Caroppo et al 2000;Polomski & Rigling 2010;Skarmoutsos & MichalopoulosSkarmoutsos 2000;Tomminen 1993). In these studies, the most pathogenic species reported was B. xylophilus followed by B. mucronatus.…”
mentioning
confidence: 99%
“…The mean number of reisolated nematodes from seedlings kept under greenhouse conditions was higher than that under outdoor conditions. Due to similarities between B. xylophilus and B. mucronatus in terms of morphology and biology, there are several reports indicating pathogenic potential of B. mucronatus with different ranges of mortality (Akbulut et al 2007b;Caroppo et al 2000;Kulinich et al 1994;Polomski & Rigling 2010). Caroppo et al (2000) used four different Bursaphelenchus species and their different isolates in a pathogenicity study.…”
mentioning
confidence: 99%